The Effectiveness of Dictogloss Technique with Text-To-Speech AI on The Listening Comprehension of the Eighth Grade Students at SMP PGRI 5 Denpasar - Ni Luh Dyah Aryani; Ni Wayan Satri Adnyani; Putu Santi Oktarina (Educational Journal, 2026)
This study aimed to find out whether students taught using the Dictogloss Technique with Text-to-Speech (TTS) AI achieved better listening comprehension than those taught using the Jumbled Sentence Technique without TTS AI. This study used a quasi-experimental design with a non-equivalent pretest-posttest control group design. The population consists of all eighth-grade students at SMP PGRI 5 Denpasar. The sample consisted of 62 eighth-grade students at SMP PGRI 5 Denpasar, namely class 8G as the experimental group with 33 students and class 8B as the control group with 29 students. The instrument used was a multiple-choice listening test. The data were collected through pre-test and post-test and analyzed using SPSS through normality test, homogeneity test, and hypothesis testing using Mann-Whitney U Test. The result showed that there was a significant difference between the two groups. The significance value was 0.019 (< 0.05). The mean score of the experimental group (93.57) was higher than the control group (86.20). This means that students in the experimental group got better results than the control group after the treatment. From this result, it can be seen that the use of Dictogloss Technique with Text-to-Speech AI gave better results compared to Jumbled Sentence Technique in learning listening. The findings of this study imply that the integration of Dictogloss Technique and Text-to-Speech AI can be considered as an effective alternative technique to improve students’ listening comprehension and support more interactive listening activities in English classrooms.